Mechanical Testing of a Novel Fastening Device to Improve Scoliosis Bracing Biomechanics for Treating Adolescent Idiopathic Scoliosis - Chloe L. Chung; Derek M. Kelly; Jeffery R. Sawyer; Jack R. Steele; Terry S. Tate; Cody K. Bateman; Denis J. DiAngelo (Applied Bionics and Biomechanics)
Velcro fastening straps are commonly used to secure a scoliosis brace around the upper body and apply corrective forces to the spine. However, strap loosening and tension loss have been reported that reduce spinal correction and treatment efficacy. A novel fastening device, or controlled tension unit (CTU), was designed to overcome these limitations. A scoliosis analog model (SAM) was used to biomechanically compare the CTU fasteners and posterior Velcro straps on a conventional brace (CB) as well as on a modified brace (MB) that included a dynamic cantilever apical pad section. Brace configurations tested were (1) CB with posterior Velcro straps, (2) CB with posterior CTU fasteners, (3) MB with posterior Velcro straps, and (4) MB with posterior CTU fasteners. MB configurations were tested with 0 N, 35.6 N, and 71.2 N CTU fasteners applied across the apical pad flap. Three-dimensional forces and moments were measured at both ends of the SAM. The CTU fasteners provided the same corrective spinal loads as Velcro straps when tensioned to the same level on the CB configuration and can be used as an alternative fastening system. Dynamically loading the apical flap increased the distractive forces applied to the spine without affecting tension in the fastening straps.